2020
DOI: 10.1038/s41392-020-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the antitumor activity of an engineered TRAIL-coated oncolytic adenovirus for treating acute myeloid leukemia

Abstract: The use of oncolytic viruses has emerged as a promising therapeutic approach due to the features of these viruses, which selectively replicate and destroy tumor cells while sparing normal cells. Although numerous oncolytic viruses have been developed for testing in solid tumors, only a few have been reported to target acute myeloid leukemia (AML) and overall patient survival has remained low. We previously developed the oncolytic adenovirus rAd5pz-zTRAIL-RFP-SΔ24E1a (A4), which carries the viral capsid protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Most of the current oncolytic adenovirus vectors insert a mutation sequence into the E1A gene, which can destroy the retinoblastoma binding domain, so that more E2F transcription factor complexes are freed from the retinoblastoma complex to regulate transcription of adenovirus in tumor cells [ 45 ]. After ensuring that adenovirus can selectively replicate in tumor cells in large numbers, the researchers integrated various exogenous genes with the function of promoting tumor cell apoptosis into the genome of the oncolytic adenovirus vector, like TNF-related apoptosis-inducing ligand (TRAIL) [ 46 ] or adenoviral death protein (ADP) [ 47 ], etc. Another type of gene that has been exploited is the prodrug activator, whose expression promotes the conversion of nontoxic prodrugs to toxic substances in the localized area of the tumor and is also delivered to nearby uninfected tumor cells through gap junctions between tumor cells, thus achieve better tumor suppressor effect [ 48 ].…”
Section: Types and Characteristics Of Ovsmentioning
confidence: 99%
“…Most of the current oncolytic adenovirus vectors insert a mutation sequence into the E1A gene, which can destroy the retinoblastoma binding domain, so that more E2F transcription factor complexes are freed from the retinoblastoma complex to regulate transcription of adenovirus in tumor cells [ 45 ]. After ensuring that adenovirus can selectively replicate in tumor cells in large numbers, the researchers integrated various exogenous genes with the function of promoting tumor cell apoptosis into the genome of the oncolytic adenovirus vector, like TNF-related apoptosis-inducing ligand (TRAIL) [ 46 ] or adenoviral death protein (ADP) [ 47 ], etc. Another type of gene that has been exploited is the prodrug activator, whose expression promotes the conversion of nontoxic prodrugs to toxic substances in the localized area of the tumor and is also delivered to nearby uninfected tumor cells through gap junctions between tumor cells, thus achieve better tumor suppressor effect [ 48 ].…”
Section: Types and Characteristics Of Ovsmentioning
confidence: 99%
“…The engineered adenoviral vector, zA4, coated by TNF-apoptosis-inducing related-ligand (TRAIL) efficiently evokes cytotoxicity and significantly inhibits leukemia-cell proliferation, and additive ginsenoside (Rh2) enforces anti-tumorgenicity by inducing the expression of TRAIL-related receptors on leukemic blasts [ 163 ].…”
Section: Therapeutic Approaches Redirecting Immuno-suppressive Micmentioning
confidence: 99%
“…Lately, Wang et al built the adenovirus rAd5pz-zTRAIL-RFP-SΔ24E1a (A4), which has the capsid protein IX connected to TNF-related apoptosis-inducing ligand (TRAIL) and causes a higher infection of tumour cells and an enhanced tumour aiming [ 107 ]. To increase the beneficial activity of A4, they produced a different form of A4, zA4, by covering A4 with further TRAIL that is combined with a leucine zipper-like dimerization domain (ZA4).…”
Section: Antitumoral Action Of Oncolytic Virusesmentioning
confidence: 99%
“…ZA4 also caused an increased anti-AML action in vivo in comparison to A4. Moreover, they demonstrated that the ginsenoside Rh2 increased the presence of TRAIL receptors and therefore increased the antineoplastic action of zA4 [ 107 ].…”
Section: Antitumoral Action Of Oncolytic Virusesmentioning
confidence: 99%